2005
DOI: 10.1111/j.1526-4610.2005.05069.x
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Stimulation Elicits a Peripheral Vestibular Imbalance in Migraine Patients

Abstract: The main result of our study is that in migraine patients painful trigeminal stimulation elicits de novo, or modifies pre-existing spontaneous Ny, generally increasing it. The finding was obtained after trigeminal stimulation, but not after median nerve stimulation. We suggest that painful trigeminal stimulation can induce an imbalance of the vestibular system in migraine patients and possibly explain their predisposition to vertigo. Our data require confirmation by other studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 30 publications
2
67
0
2
Order By: Relevance
“…An interesting aspect is represented by the reciprocal connections between the vestibular and trigeminal-vascular pathways, thus producing a close association between vestibular and trigeminal information (22). Trigeminal stimuli may activate the vestibular system in patients with migraine but not in controls (36).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting aspect is represented by the reciprocal connections between the vestibular and trigeminal-vascular pathways, thus producing a close association between vestibular and trigeminal information (22). Trigeminal stimuli may activate the vestibular system in patients with migraine but not in controls (36).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the central vestibular system could be involved in the migraine attack, during which there is activation of some brainstem nuclei [Weil ler et al, 1995] or a possible diffusion of spreading depression to them [Mraovitch et al, 1992]. Stimulation of the trigeminal nerve has been shown to provoke nystagmus in migraineurs [Marano et al, 2005]. The fact that no patients in this study experienced symptoms other than vertigo traditionally associated with basilar migraine, such as diplopia, hemifacial numbness or weakness, suggests that the vertigo may not necessarily be secondary to activating brainstem nuclei in all cases of vestibular migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions associated with vestibular structures commonly produce nystagmus. Marano et al (2005) reported that spontaneous nystagmus developed more readily in migraine sufferers than in controls following unilateral electrical stimulation of the supraorbital region of the forehead, suggesting that trigeminal nerve activity evoked vestibular dysfunction in migraineurs.…”
Section: Vestibular Symptomsmentioning
confidence: 99%